Simulasi Pengendalian Limpasan Permukaan dengan Penerapan Low-Impact Development di Kawasan Perumahan: Simulation of Surface Runoff Control with Low-Impact Development Implementation in Residential Area - Yuono, Agus Lestari; Iryani, Sakura Yulia; Alia, Febrinasti; Al Amin, Muhammad Baitullah (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2024)
Applying the Low-Impact Development (LID) approach in urban drainage systems can help control surface runoff, therefore mitigating the potential of flooding risk. However, its effectiveness varies widely, and various technical factors influence its performance. This study aims to determine the effectiveness and performance of LID units, namely bioretention and infiltration wells, in controlling surface runoff. The Center Park Housing area, covering an area of ​​11.53 hectares located in Palembang City, was chosen as the study area. The ability of the LID unit to reduce the volume and discharge of runoff, as well as the runoff coefficient, was simulated using the Storm Water Management Model (SWMM) program based on input from various design rainfall cases. There were four simulated design rainfalls, i.e. 108.76 mm (2-year return period), 133.20 mm (5-year), 149.38 mm (10-year), and 169.82 mm (25-year). The LID unit implementation scenarios were varied with the number of infiltration well units of 1 - 4 units per house plot. The number and area of ​​bioretention units were considered constant for all scenarios. The simulation results show that the LID implementation can reduce runoff volume and peak discharge and help decrease the runoff coefficient in the study area effectively, especially in the case of lower design rainfall (2-year). The performance of the infiltration wells unit in producing runoff losses is better than the bioretention unit because its construction structure has a larger storage capacity for a similar unit area. Although the LID method is quite effective in reducing runoff, its combination with conventional methods may produce better performance, so further research that discusses this needs to be addressed.